2022
DOI: 10.1038/s41408-022-00732-3
|View full text |Cite
|
Sign up to set email alerts
|

Defining new reference intervals for serum free light chains in individuals with chronic kidney disease: Results of the iStopMM study

Abstract: Serum free light chain (FLC) concentration is greatly affected by kidney function. Using a large prospective population-based cohort, we aimed to establish a reference interval for FLCs in persons with chronic kidney disease (CKD). A total of 75422 participants of the iStopMM study were screened with serum FLC, serum protein electrophoresis and immunofixation. Estimated glomerular filtration rate (eGFR) was calculated from serum creatinine. Central 99% reference intervals were determined, and 95% confidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…It should be remembered that falling GFRs have a differential effect on the clearance of kappa (monomers) and lambda (dimers) FLC causing the polyclonal kappa: lambda FLC ratio to increase, although this increase varies between methods for measuring FLC. For example, with the FREELITE™ method, the normal FLC ratio is 0.54–3.30 for an eGFR <30 mL/min 25 …”
Section: Risk Stratification Of Monoclonal Gammopathy Of Undetermined...mentioning
confidence: 99%
“…It should be remembered that falling GFRs have a differential effect on the clearance of kappa (monomers) and lambda (dimers) FLC causing the polyclonal kappa: lambda FLC ratio to increase, although this increase varies between methods for measuring FLC. For example, with the FREELITE™ method, the normal FLC ratio is 0.54–3.30 for an eGFR <30 mL/min 25 …”
Section: Risk Stratification Of Monoclonal Gammopathy Of Undetermined...mentioning
confidence: 99%
“…Optilite iStopMM CKD pts 2002 [8] 2007 [9] 2013 [10] 2018 [11] 2017 [12] 2020 [13] 2022 [1] 2022 [1] 2022 [1] 2021 [7] (n=282…”
Section: Optilite Healthy Controls Bnii Healthy Controlsmentioning
confidence: 99%
“…With great interest we have read the publication of Long et al in which they propose new reference intervals for serum free light chain (FLC) ratios in individuals with chronic kidney disease [ 1 ]. The kidney reference interval for FLC-ratio was introduced after Hutchison et al showed that both the serum FLC concentrations and the FLC-ratio increased with worsening kidney function [ 2 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by Stern and colleagues, an abnormal FLC ratio has since been shown to predict risk of MGUS progression and can also be diagnostic of light‐chain MGUS 1 . However, the FLC ratio is not sensitive for MGUS overall and is affected by renal function, and even though recently defined renal reference ranges improve the accuracy of the FLC ratio, it should be used in conjunction with traditional electrophoresis methods at this time 11 . In the last few years, a completely new way to detect monoclonal immunoglobulins by mass spectrometry (MS)‐based diagnostics has emerged as a potential replacement to Dr. Waldenström's SPEP.…”
mentioning
confidence: 99%